Multidimensional Assessment and Alleviation of Global Energy Poverty Aligned With UN SDG 7 - Che, Xiahui; Jiang, Minxing; Fan, Cheng (Frontiers in Energy Research, 2021)
There are increasing concerns that energy poverty across nations is weakening the global efforts toward achieving Sustainable Development Goals (SDGs). A systematic assessment of energy poverty is, therefore, essential to track the spatiotemporal pattern of SDG 7 and monitor the global efforts in alleviating energy poverty. This article develops the first Multidimensional Energy Poverty Assessment Index (MEAI), incorporating energy availability, affordability, and efficiency applicable to quantify the spatiotemporal dynamics of energy poverty development at global, regional, and national scales. Our analyses indicate that the overall MEAI and indices in all dimensions decreased from 2001 to 2016 at a global level with energy affordability experiencing the highest decline. The MEAI at the national level declines within the same period, showing significant regional heterogeneity in terms of the sub-index. Energy efficiency in developed and less-developed regions is characterized by high carbon emissions and low energy modernization, respectively. The energy availability indices are lower in developed nations and in nations with abundant energy resources. Overall, our results highlight a sudden increase in MEAI for Central America in 2014 and a gradual decline in MEAI for East Asia during 2014–2016. A call for regional actions is critically needed to solve energy poverty from different facets.